2016
DOI: 10.1021/acscatal.6b01227
|View full text |Cite
|
Sign up to set email alerts
|

A Career in Catalysis: Masakatsu Shibasaki

Abstract: Professor Masakatsu Shibasaki's distinguished scientific accomplishments in the field of asymmetric catalysis are compiled here with particular emphasis on multimetallic cooperative catalysis. In 1992, he discovered revolutionary multimetallic chiral complexes composed of a rare earth metal, alkaline metals, and 1,1′-binaphthyl-2-binaphthols (BINOLs) that promoted a number of enantioselective reactions in a highly efficient and stereoselective manner. This finding resulted in chiral multimetallic catalysts tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 180 publications
0
22
0
Order By: Relevance
“…[5,6] In traditional organic synthesis, several lanthanide-based molecules, such as SmI 2 (samarium iodide) and (NH 4 ) 2 Ce(NO 3 ) 5 (CAN, ceric ammonium nitrate), are widely applied for stoichiometric usage as reductant or oxidant. [11][12][13] Considering the oxidation state of lanthanides, the trivalent cation is the general oxidation state for all metals. The Mukaiyama aldol reaction and catalytic Diels-Alder reactions are representative organic transformations catalyzed by lanthanides.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5,6] In traditional organic synthesis, several lanthanide-based molecules, such as SmI 2 (samarium iodide) and (NH 4 ) 2 Ce(NO 3 ) 5 (CAN, ceric ammonium nitrate), are widely applied for stoichiometric usage as reductant or oxidant. [11][12][13] Considering the oxidation state of lanthanides, the trivalent cation is the general oxidation state for all metals. The Mukaiyama aldol reaction and catalytic Diels-Alder reactions are representative organic transformations catalyzed by lanthanides.…”
mentioning
confidence: 99%
“…[7][8][9][10] Lanthanide-based multimetallic catalysis for asymmetric synthesis has also been intensively developed, including bimetallic Schiff base complexes. [11][12][13] Considering the oxidation state of lanthanides, the trivalent cation is the general oxidation state for all metals. [14] However, some metals, such europium, samarium, and ytterbium, can exist in both 2 + and 3 + oxidation states.…”
mentioning
confidence: 99%
“…We next investigating other types of catalytic cascade reaction sequences involving other types of direct enantioselective C‐C bond‐forming reactions, which proceed via enamine activation of an unmodified aldehyde (Scheme ). Thus, the catalytic Mannich or aldol reaction, , between a saturated aldehyde 8 and imine 9 or acceptor 10 was linked with cascade sequences involving an aminothiol 4 to give the corresponding bicyclic α‐amino‐γ‐lactam N , S ‐acetal 11 (Table ) or α‐hydroxy‐γ‐lactam N , S ‐acetal ent ‐ 11′ (Table ), respectively. We found that performing the Mannich reaction between aldehydes 8 and N ‐ para ‐methoxyphenyl (PMP) protect imine 9 in butanol followed by addition of 4a gave the corresponding bicyclic γ‐lactam N , S ‐acetals 11 with excellent ee values in one pot.…”
Section: Resultsmentioning
confidence: 99%
“…It significantly reduces waste generation, separation steps and use of solvents. There are several ways of catalyzing direct asymmetric C–C or C–hetero‐atom bond forming reactions of carbonyl compounds . In this context, asymmetric amine catalysis is a powerful methodology with a plethora of reactions and different type of cascade transformations in its tool‐box .…”
Section: Introductionmentioning
confidence: 99%
“…α-Halogenated 7-azaindoline amides are particularly useful in direct enolization chemistry due to their facilitated enolization in soft Lewis acid/Brønsted base cooperative catalysis allowing for direct aldol and Mannich-type reactions with chiral Cu(I) catalysts in a highly stereoselective manner. [227] Eventually, the discovery of practical methods for the introduction of difluoroalkyl groups into target molecules continue to be a challenging topic. [228] Protocols working under metal free conditions and showing wide substrate scope are still highly desirable.…”
Section: Discussionmentioning
confidence: 99%